Peningkatan Daya Imajinasi Melalui Menulis Kreatif Pantun Pada Siswa Kelas IV SD Negeri Kebondalem Kidul I Klaten - Srinugraheni, Aninditya; A.S., Dhyajeng (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2016)
The purpose of this research is to increase the power of imagination of learners SDN Kebondalem Kidul I Klaten through learning creative writing poem. Poem is one type of fiction, in writing the poem takes its own imagination, because the lines in the poem have a different meaning, The first and second rows in the form called sampiran rhymes, he third and fourth lines rhyme form of content, Sampiran and the content of the poem have a different meaning and are not related to each other. The absence of a link on the contents of the poem sampiran and require thought and imagination of its own. therefore, researchers conducted the study in SDN Kebondalem Kidul I Klaten. Subjects in this study were 10 students in grade IV SDN Kebondalem Kidul I Klaten. The Data collection techniques ware used is interviews and tests of the work of students in writing a poem. The results showed that the power of imagination comparable to the creativity of learners writing poem. It can be concluded that the increase in the imagination of learners can be done through creative writing poem on the learner SDN Kebondalem Kidul I Klaten.